RESISTANCE OF SEVERAL RICE VARIETIES AGAINST THE BACTERIAL PANICLE BLIGHT DISEASE (BURKHOLDERIA GLUMAE) - Wahidah, Nurni; Safni, Irda; Hasanuddin, Hasanuddin; Lisnawita, Lisnawita (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Resistance of Several Rice Varieties against the Bacterial Panicle Blight Disease (Burkholderia glumae) .Burkholderia glumae is included as A2 Quarantine Plant Pest Organism, which is found in some restricted area in Indonesia.  B. glumae is a seedborne pathogen that causes panicle blight, seedling rot, grain rotand leaf sheath browning on rice plants. This research was objected  to determine the resistance of five  rice varieties against bacterial panicle blight pathogen. The experiment was carried out at the screen house of Faculty of Agriculture, Universitas Sumatera Utara, Medan from May to September 2018. This experiment was designed using Factorial Completely Randomized Design (CRD) with 2 factors; Factor 1: B1 (sterile water as negative control), B2 (B. glumae isolate CH BJ), B3 (B. glumae isolate IR 64), B4 (B. glumae isolate IC PRC), B5 (B. glumae isolate DSMZ 9512? as positive control). Factor 2: V1 (Cisokan variety), V2 (Inpari 4 variety), V3 (Situbagendit variety), V4 (Inpari 32 variety) and V5 (Cidenu variety). The results showed that all five rice varieties were highly susceptible to bacterial panicle blight pathogen. Inpari 32 variety had the highest number of seeds and weight of 100 seeds and had the lowest percentage of empty seeds.  IR 64 variety had the lowest number of seeds and the weight of 100 seeds and had the highest percentage of empty seeds.